A role for nitric oxide-driven retrograde signaling in the consolidation of a fear memory - Overeem, Kathie A.; Ota, Kristie T.; Monsey, Melissa S.; Ploski, Jonathan E.; Schafe, Glenn E. (Frontiers in Behavioral Neuroscience, 2010)
In both invertebrate and vertebrate models of synaptic plasticity, signaling via the putative “retrograde messenger” nitric oxide (NO) has been hypothesized to serve as a critical link between functional and structural alterations at pre- and postsynaptic sites. However, while in vitro models of synaptic plasticity have consistently implicated NO signaling in linking postsynaptic induction mechanisms with accompanying presynaptic changes, a convincing role of such “retrograde signaling” in mammalian memory formation has remained elusive. Using auditory Pavlovian fear conditioning, we show that synaptic plasticity and NO signaling in the lateral nucleus of the amygdala (LA) regulate the expression of the ERK-driven immediate early gene early growth response gene I (EGR-1) in regions of the auditory thalamus that are presynaptic to the LA. Further, antisense knockdown of EGR-1 in the auditory thalamus impairs both fear memory consolidation and the training-induced elevation of two presynaptically localized proteins in the LA. These findings indicate that synaptic plasticity and NO signaling in the LA during auditory fear conditioning promote alterations in ERK-driven gene expression in auditory thalamic neurons that are required for both fear memory consolidation as well as presynaptic correlates of fear memory formation in the LA, and provide general support for a role of NO as a “retrograde signal” in mammalian memory formation.